Study on Dynamic Characteristic and Sensitivity Analysis of Stern Bearing based on Harmonic Response Analysis - Shenwen Long; Youqiang Wang; Yabo Zhou; Cong Wei (Jixie chuandong, 2019)
In order to solve the problem of resonance and sound in the running process of water lubricated rubber stern bearing， the dynamic response analysis of stern bearing is carried out based on ANSYS finite element analysis platform. Firstly， the low order natural frequencies and modes of stern bearing are obtained by modal analysis. Secondly， the response rule of the stern bearing with the frequency change is obtained by using the harmonic response analysis， so the natural frequencies which affect the dynamic characteristics of the stern bearing are determined. Finally， the sensitivity analysis of the structural parameters is carried out， and the influence factors of the vibration characteristics are sorted， the basis for reducing the experimental cost and the dynamic design of stern bearing is provided.